2010
DOI: 10.1111/j.1365-2265.2010.03883.x
|View full text |Cite
|
Sign up to set email alerts
|

Depot‐ and ethnic‐specific differences in the relationship between adipose tissue inflammation and insulin sensitivity

Abstract: Black South African women had higher inflammatory gene expression levels than white women; however, the relationship between AT inflammation and S(I) was stronger in white compared to black women. Further research is required to explore other factors affecting S(I) in black populations. Contrary to our original hypothesis, gluteal SAT had a greater inflammatory gene expression profile than abdominal SAT depots. The protective nature of gluteo-femoral fat therefore requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 39 publications
4
70
1
1
Order By: Relevance
“…2,[15][16][17][18][19][20][21][22][23] However, this message is further muddied by new reports that demonstrate that truncal SQF adipose tissue may actually aid in the metabolic changes that occur with obesity as this depot supplies a greater percentage of adipose tissue compared with the VAT and that the protective effects of SQ fat is limited more to the gluteal femoral SQ depot (or the so-called "pear-shape"). 11,15,[24][25][26][27][28] The protective action of gluteal femoral SQF seems to be further limited to the femoral subcutaneous region and not necessarily with the gluteal region in black South African women further confounding the issue with ethnicity differences. 11,16,25,27,[29][30][31][32] Indeed, even gender appears to have a profound influence on the responses by different adipose depots.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,[15][16][17][18][19][20][21][22][23] However, this message is further muddied by new reports that demonstrate that truncal SQF adipose tissue may actually aid in the metabolic changes that occur with obesity as this depot supplies a greater percentage of adipose tissue compared with the VAT and that the protective effects of SQ fat is limited more to the gluteal femoral SQ depot (or the so-called "pear-shape"). 11,15,[24][25][26][27][28] The protective action of gluteal femoral SQF seems to be further limited to the femoral subcutaneous region and not necessarily with the gluteal region in black South African women further confounding the issue with ethnicity differences. 11,16,25,27,[29][30][31][32] Indeed, even gender appears to have a profound influence on the responses by different adipose depots.…”
Section: Introductionmentioning
confidence: 99%
“…11,15,[24][25][26][27][28] The protective action of gluteal femoral SQF seems to be further limited to the femoral subcutaneous region and not necessarily with the gluteal region in black South African women further confounding the issue with ethnicity differences. 11,16,25,27,[29][30][31][32] Indeed, even gender appears to have a profound influence on the responses by different adipose depots. 16,[32][33][34] One mechanism that seems universal in human adipose depot regulation of adipose tissue is insulin, although, with as much variation within one species (human) one can only imagine the differences which exist between species.…”
Section: Introductionmentioning
confidence: 99%
“…The finding that GSAT displays a less inflammatory profile in obesity contrasts with previous reports that inflammation is either the same as (44) or higher than (45) ASAT. However, unlike the global approach used here, those observations were based on gene-specific approaches (44,45). Furthermore, in addition to the transcriptional analyses, we performed in vivo measurements of regional cytokine release.…”
Section: Regional Inflammatory and Metabolic Profiles Of Atmentioning
confidence: 99%
“…Genetic studies have shown that African American and sub-Saharan populations are more likely to carry allelic variants that up-regulate inflammation compared with white women [28], and in a SA population, black women had higher subcutaneous adipose tissue (SAT) TNFa gene expression than white SA women [6]. Further, white SA women have been reported to have lower dietary fat intake, but a higher relative intake of saturated fat (SFA) and lower intake of PUFA than black women [11].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, there are differences in the distribution of inflammatory gene polymorphisms, inflammatory gene expression and dietary fat intake between black and white populations [2,6,11]. Genetic studies have shown that African American and sub-Saharan populations are more likely to carry allelic variants that up-regulate inflammation compared with white women [28], and in a SA population, black women had higher subcutaneous adipose tissue (SAT) TNFa gene expression than white SA women [6].…”
Section: Introductionmentioning
confidence: 99%